Analisis Pengaruh Upah Minimum Provinsi, Investasi dan Ekspor Terhadap Penyerapan Tenaga Kerja di Pulau Jawa 2013-2022 - Ade Aprilia Sasi Lestari; Dicky Iranto; Agus Wibowo (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Java Island, as the most populous island in Indonesia, cannot be separated from employment problems. The problems faced include an increase in the labor force that is higher than labor absorption. Efforts to increase labor absorption are of course inseparable from the factors that influence it, such as the provincial minimum wage, investment and exports. This research aims to determine the influence of provincial minimum wages, investment and exports on labor absorption on Java Island in 2013-2022, both partially and simultaneously. This research is a type of research with a quantitative approach. The data used is secondary data from 6 provinces on the island of Java (DKI Jakarta, West Java, Banten, Central Java, Special Region of Yogyakarta and East Java) for 2013-2022. The analysis used is panel data regression analysis with the Common Effect regression model. The data was processed using Eviews 12. The research results show that: 1) The provincial minimum wage partially has a positive and significant effect on labor absorption; 2) Partial investment does not have a significant effect on labor absorption; 3) Exports partially have a positive and significant effect on labor absorption; 4) Provincial minimum wages, investment and exports simultaneously have a significant effect on labor absorption.